Overload Impact Analysis On The Pavement Design Life of Toll Roads (Case Study: Tangerang-Merak Toll Road Segment KM 71+000 to KM 77+000 Towards Jakarta) - Rindu Twidi Bethary; Dwi Esti Intari; Arief Budiman; M. Raslin Hudaya; Muhammad Fakhruriza Pradana; Wiwien Suzanti (JURUSAN TEKNIK SIPIL, 2026)
The Tangerang–Merak Toll Road section from KM 71+000 to KM 77+000 in the direction of Jakarta plays an important role in the distribution of industries from Anyer, Cilegon, and surrounding areas. However, the high volume of ODOL (Over Dimension Over Load) vehicles causes excessive loads exceeding the pavement’s design capacity, accelerating damage, reducing design life, increasing maintenance costs, and endangering safety. An analysis is needed to determine the impact of excessive loads on pavement design life on this section. This study aims to determine traffic volume and analyze the impact of overloaded vehicles on pavement design life using the AASHTO 1993 and MDPJ 2024 methods for VDF calculations. Data from the 2024 LHR shows a total of 8,090,694 vehicles, consisting of 97.71% normal vehicles and 2.29% overloaded vehicles. The VDF values for normal vehicles in categories 1–5 are 1.86; 1.83; 1.68; 2.58; and 1.45. Meanwhile, the VDF for overloaded vehicles is 1.86; 1.95; 16.10; 3.03; and 1.96. Class 3 vehicles tend to be overloaded, resulting in a high VDF. The design life of the road with normal vehicles is 5 years (truck factor 1.46), but it decreases to 2.275 years due to overloading (truck factor 3.55). Overloading and uneven distribution accelerate damage and reduce the road’s design life. Simulations of 5%, 10%, and 15% increases in overloaded vehicles reduce design life to 2.176; 2.087; and 2.005 years, respectively. This demonstrates that overloaded vehicles significantly impact the reduction of road design life.